RACIAL/CULTURAL IDENTITY: TRANSFORMATION AMONG SCHOOL‐BASED MENTAL HEALTH PROFESSIONALS WORKING IN NUNAVUT - Wihak, Christine; Merali, Noorfarah (Canadian Journal of Education/Revue canadienne de l'éducation, 2007)
Eight non‐Aboriginal school counselors, who temporarily lived in Nunavut to provide services to Inuit clients, were interviewed regarding changes in their sense of self and their racial/cultural identity as a result of cross‐cultural immersion. They were also engaged in an arts‐based exercise where they pictorially represented perceived self‐changes. Analysis of counsellors’ narratives of their experiences in Nunavut and their art work revealed an increasing awareness of their “Whiteness” and their participation in the colonizing culture. The counsellors also displayed changes in cultural worldview that directly paralleled the socio‐centric and eco‐ centric nature of the Inuit culture, precipitating culturally sensitive counselling practice. Key words: racial/cultural identity; whiteness; Aboriginal; school counselling; multicultural competence Huit conseillers pédagogiques non autochtones temporairement en poste au Nunavut pour fournir des services à une clientèle inuite ont été interviewés au sujet de l’évolution de leur perception de leur identité personnelle et raciale/culturelle à la suite de leur immersion dans une autre culture. Ces conseillers ont également participé à un exercice créatif dans le cadre duquel ils devaient représenter en images les changements qu’ils avaient perçus chez eux. L’analyse des propos de ces conseillers au sujet de leurs expériences au Nunavut et de leurs créations ont révélé une conscientisation accrue de leur appartenance à la race blanche et de leur participation à une culture colonisatrice. Les auteurs notent également que la vision du monde de ces conseillers pédagogiques a changé et ce, en lien direct avec la nature sociocentrique et écocentrique de la culture inuite, ce qui a favorisé une prestation de services tenant compte des différences culturelles. Mots clés: identité raciale/culturelle, race blanche, autochtones, conseiller pédagogique, compétence multiculturelle